(untitled) (European Journal of Education and Psychology, 2019)
There have been many different instruments that have been developed in Anglo-Saxon countries in order to evaluate school climate. However, it doesn’t exist yet a widely accepted and validated measurement instrument in Spanish that evaluates in a balanced way, through different dimensions, the main aspects that most researches defend as components of the school climate. With the purpose of overcoming this limitation, the objective of this study is to elaborate a new measurement instrument of the perception of the school climate and to analyze its construct and convergent validity. A total of 480 students from Álava and Madrid of ages between 12 and 18 (M = 14.91, SD= 1.49), take part in the research; 286 (59.6%) of them were women and 194 (40.4%) men. The participants filled in two questionnaires: PACE (school climate) and the version adapted to Spanish of the School Engagement Measure. The analyses carried out allow selecting the most appropriate items for the multidimensional measurement of the school climate. The questionnaire presents adequate internal consistency and external validity. Thus, the new questionnaire gets to surpass the limitation of other measurement instruments created previously and the procedure to be followed in order to continue with its validation is under discussion.